The effect of rapid blood pressure control on P-wave dispersion in hypertensive urgency - Karaca, Ilgin; Durukan, Polat; Dagli, Necati; Yavuzkir, Mustafa; Ikizceli, Ibrahim; Balin, Mehmet (Springer, 2008)
A sharp increase in blood pressure, increase in atrial pressure and atrial strain, left ventricular diastolic dysfunction, and left ventricular hypertrophy (LVH) lead to heterogeneity and instability in atrial conduction. The resulting physiopathological situation may elevate maximum Pwave duration (P-max) and P-wave dispersion (PWD) in electrocardiography. The objective of our study was to explore the effect of the sudden change in atrial hemodynamics on P-max and PWD, which may indicate the risk of atrial fibrillation (AF) development in hypertensive urgency. The study included patients diagnosed as hypertensive urgency (systolic blood pressure a parts per thousand yen180 mmHg, diastolic blood pressure a parts per thousand yen110 mmHg). Nitroprusside was started at a dose of 0.2 mu g/kg/min, and the ensuing dose was arranged according to blood pressure. Echocardiography and electrocardiography were used to noninvasively measure changes in diastolic function and PWD and P-max, respectively. The study enrolled 102 patients (mean age 57.9 +/- 11.6 years; 32 [31.4%] males, and 70 [68.6%] females). P-max decreased from 99.9 +/- 11.1 msec (95% confidence intervals [CI] 97.7, 102) to 88.5 +/- 9.3 msec (95% CI 86.6, 90.3) (P < 0.001), while PWD decreased from 60.1 +/- 7.4 msec (95% CI 58.7, 61.6) to 43.9 +/- 6.7 msec (95% CI 42.5, 45.2) (P < 0.001). In addition, most patients had LVH and diastolic dysfunction. After nitroprusside treatment improvements in indicators of diastolic functions such as E/A ratio, deceleration time, and isovolumetric relaxation time were observed. The change observed in P-max and PWD in hypertensive urgency may be associated with the rapid change in blood pressure and atrial strain, sympathetic nervous system activation, relative myocardial ischemia, and left ventricular diastolic dysfunction. Rapid regulation of blood pressure with nitroprusside brought about a marked decrease in P-max and PWD in our patients. This improvement was interpreted as atrial conduction acquiring a stable and homogeneous character, which may reduce the risk of AF development in hypertensive urgency.
Keywords: hypertensive urgency; maximum P-wave duration; nitroprusside; P-wave dispersion